Análise do comportamento bilíngue: estudos teóricos e empíricos - Santos, Rafael Ernesto Arruda (2020)
This dissertation is divided into five chapters. The first one is theoretical, the second and third ones are systematic reviews and the fourth and fifth ones are empirical studies. Chapter 1 aims to analyze a theoretical approach concerning Behavior Analysis and Bilingualism to value the cultural aspects involved in sign language and the deaf community. In the cultural context, the deaf differs when modeling their language, while they are visually modeled for the execution of signs, the listeners are modeled in speech, thus producing two distinct verbal communities: deaf and listeners. The conclusion produces a reflection on whether the practice of the Behavior Analyst, as a cultural agent, should promote a medical or an anthropological vision in his/her studies on deafness, which could lead to the approximation with Bilingualism in the defense of Libras and the deaf Community. Chapters 2 and 3 aimed to analyze papers published on deafness / hearing impairment in Behavior Analysis national (Chapter 2) and international (Chapter 3) journals,. These two chapters carried out a systematic review. The results of Chapter 2 present 39 papers, 18 of which are on deafness / hearing impairment, 18 on Autism Spectrum Disorder and three on intellectual disability. In Chapter 3, 30 papers were found, being 23 on empirical research and seven on theoretical research. The data presents a historical tradition of papers on Behavior Analysis and deafness or hearing impairment. Chapter 4 aimed to verify the effect of Matching-to-sample (MTS) trials as a procedure for evaluating a pre-established reading repertoire with word comprehension in deaf adolescents, by choosing the printed word corresponding to the video with sign in Libras. The method consisted of first testing identity MTS with colors to acclimate the participant to the experiment; then, MTS trials were used to test arbitrary relations between signs in Libras (A) as samples and printed words (B) in Portuguese as comparisons; finally, the participants were instructed to choose the correct order (as programmed by the experimenters) of words to form sentences in Portuguese and in Libras. Chapter 5 aimed to establish contextual color control for the syntactic configuration of two languages, green as contextual control for sentences in Libras and yellow as contextual control for sentences in Portuguese through teaching with copy. Four adolescents from a bilingual school and users of Libras participated in the study. The experimental method consisted of a multiple baseline design with multiple probes, in which pre-tests evaluated the performance of constructing recombined sentences and sentences that were to be taught. In summary, the teaching procedures of Behavior Analysis collaborate to seek empirical data on Bilingualism and to reflect on theoretical interpretations of verbal behavior and Bilingualism.